Assessment on India’s involvement and capacity-building in Arctic Science - Pareek, Nikhil (Polar Research Institute of China - PRIC, 2021)
India became an observer in Arctic Council in 2013 and has three research stations operational in the poles, including “Maitri” commissioned in 1989 and “Bharati” commissioned in 2012 at Antarctic and “Himadri” at Arctic. Though the Government of India has consistently been extending full support to the research endeavours yet the same is bogged by inadequate research output, lack of dedicated polar research vessel and other bureaucratic bottlenecks. A massive void in the Indian scientific pursuits is that India does not possess a polar research vessel or an icebreaker and has to rely on chartered vessels, seriously limiting its research timeframe as well as huge economic drain and thus compromising the scientific research. This cleft in the professed research narrative despite having a physical presence for over 3 decades in the polar regions and the proposal for acquisition of a polar research vessel having been approved in June 2010 yet the same is yet to be operationalised which is seriously impinging the scientific research as well as the professed commitment to Arctic research. Recently, India has released its draft Arctic Policy and had sought public comments thereon till 26 January 21 before its finalisation. India’s draft policy reiterates the oft stated goals of scientific research, connectivity, global governance and international cooperation, and human development with emphasis on Indian human resource pool. The inspiration of a delayed Indian policy on the High North appears to be the Chinese white paper of 2018. The scientific pursuits can propel the strategic engagement in the region to greater levels by extensive collaboration and cooperation with several other nations present there. Indian attempts so far have remained acutely short of the promise and India should build on its strengths for obtaining a leadership position in this strategically vital and economically lucrative region.